Justice In Her Labyrinth: Doctrinal Reasoning, Lacanian Psychoanalysis, and Legal Formalism's Problem of the Subject - McTiernan, Daniel R. (University of Pittsburgh law review, 2024)
In this Note, Lacanian psychoanalysis provides a model for approaching what Pierre Schlag called “The Problem of the Subject” in contemporary legal thought. Schlag argued that all schools of contemporary legal thought “establish, depend upon, and eclipse a quintessentially liberal individual subject.” David Caudill has posited Lacanian psychoanalysis as a framework for accounting for an irrational subject of law. This Note expands on Caudill’s work by applying Lacan’s linguistics of the unconscious to solve the “Problem of the Subject” in legal formalism. In conjunction with Jessie Allen’s scholarship casting doctrinal reasoning as a disruptive psychological practice, Lacanian psychoanalysis may account for the “eclipsed” subject of legal formalism without undoing legal formalism’s core tenets.